Magnetohydrodynamic channel flow and variational principles - Adnan A. El-Hajj (International Journal of Mathematics and Mathematical Sciences)
This paper deals with magnetohydrodynamic channel flow problems. Attention is given to a variational principle where the boundary conditions are incorporated via a suitable functional which is stationary at the solution of the given problem; the trial functions used for the approximate solution need not satisfy any of the given boundary conditions.